Evolution of the peroxide-induced degradation of polypropylene along a twin-screw extruder : experimental data and theoretical predictions - Berzini, F. (2006)
This article reports an experimental and theoretical study of the peroxide-induced degradation of polypropylene in a corotating twin-screw extruder. Experiments were performed with different peroxide concentrations and different operating conditions. The evolution of the chemical reaction along the extruder was monitored with specific sampling devices. Material changes were characterized by rheological measurements and via the determination of the molecular weights of samples collected at the same locations. The theoretical results were obtained with a model that coupled the interactions between flow conditions encountered in the extruder, the kinetics of the reaction, and the changes in the viscosity induced by changes in the molecular weight. The experimental results evidenced the relationships between the process conditions (peroxide concentration and processing parameters) and material properties (rheological properties and molecular structure of the modified polypropylene). Good agreement between the theoretical and experimental results was obtained